Kelalaian Tanggung Jawab Suami Sebagai Alasan Gugat Nafkah Madliyah Tanpa Adanya Perceraian - Qoidul Khoir (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2020)
This article aims to describe the review of Islamic law on the obligations of a father who abandoned the maintenance of the child in the decision of the Supreme Court number 608/K/AG/2003 and describing a living madliyah children after divorce based on the protection of children's rights in Law Number 23 Year 2002 on the Protection of Children. This research is included in the type of normative legal research, using a statutory approach and a conceptual approach. The processing of legal materials in normative legal research is by means of literature studies which are described and then linked between one legal material and other legal materials, especially the relationship between the elements covered in the research problem. So it is presented in a systematic writing form to answer the problems that have been formulated in this research. The result showed that the duty of a father to meet child support does not become payable if the elapsed time, but it could be due to maintenance if there is a decision of the judge. This imposition on the grounds that the father in condition to be able to work deliberately remiss. Supreme Court Decision No. 608/K/AG/2003 does not conflict with Islamic law. Every parent has an obligation to be responsible for nurturing, nurture, educate, and protect children. Deliberateness of a father neglects the obligation to provide maintenance, so that children can not get their rights and suffer a loss, then it can be described as acts of negligence as regulated in Law Number 23 of 2002 on the Protection of Children